Contexto climático y parámetros meteorológicos en las Tanusas - Puerto Cayo, Manabí – Ecuador - Esteves Olvera, Diana Milena (2025)
This study evaluated the climatic context and meteorological parameters in Las Tanusas – Puerto Cayo, Manabí, Ecuador, aiming to identify thermal and pluviometric patterns, analyze correlations between meteorological variables, and propose climate change adaptation strategies. Historical data from NASA (1981–2024) and future projections for three time horizons (2010–2039, 2040–2069, and 2070–2099) were used. The results showed an increase in temperature, as well as variability in precipitation, intensified by climatic phenomena such as El Niño and La Niña. Significant correlations were also identified between variables such as humidity, atmospheric pressure, and temperature, which facilitated a better understanding of local climate behavior. Finally, a guide of community adaptation strategies was developed, focusing on reducing climate vulnerability in Las Tanusas through environmental education and sustainable planning.